ABO blood type association with SARS‐CoV‐2 infection mortality: A single‐center population in New York City. Issue 4 (5th March 2021) - Szymanski, James; Mohrmann, Laurel; Carter, Jamal; Nelson, Randin; Chekuri, Sweta; Assa, Andrei; Spund, Brian; Reyes‐Gil, Morayma; Uehlinger, Joan; Baron, Sarah; Paroder, Monika
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has a variable clinical course with significant mortality. Early reports suggested higher rates of SARS‐CoV‐2 infection in patients with type A blood and enrichment of type A individuals among COVID‐19 mortalities. Study Design and Methods: The study includes all patients hospitalized or with an emergency department (ED) visit who were tested for SARS‐CoV‐2 between March 10, 2020 and June 8, 2020 and had a positive test result by nucleic acid test (NAT) performed on a nasopharyngeal swab specimen. A total of 4968 patients met the study inclusion criteria, with a subsequent 23.1% (n = 1146/4968) all‐cause mortality rate in the study cohort. To estimate overall risk by ABO type and account for the competing risks of in‐hospital mortality and discharge, we calculated the cumulative incidence function (CIF) for each event. Cause‐specific hazard ratios (csHRs) for in‐hospital mortality and discharge were analyzed using multivariable Cox proportional hazards models. Results: Type A blood was associated with the increased cause‐specific hazard of death among COVID‐19 patients compared to type O (HR = 1.17, 1.02–1.33, p = .02) and type B (HR = 1.32, 1.10–1.58, p = .003). Conclusions: Our study shows that ABO histo‐blood group type is associated with the risk of in‐hospital death in COVID‐19 patients, warranting additional inquiry. Elucidating the mechanism behind this association may reveal insights into the susceptibility and/or immunity to SARS‐CoV‐2.